Influence of the Method Used in the Generation of Valid Engineering Concepts - Torres-Benoni, F (Springer-Verlag France, 2019)
Innovative products are almost a necessity nowadays; however, educational institutions do not have reliable data about which methods should be instructed, nor how. For this reason, the objective of this research is to quantify the relevance of the selected design method when generating concepts in the early stages of design. To compare the performance of structured and intuitive methods to generate ideas, a two-stage experiment was applied in two contexts in which were evaluated novelty, variety, quality and quantity. First, participants were asked to solve a problem using a recently taught method. The aim was to obtain insights about the influence of each method. Second, all participants were asked to solve a new problem after being taught four chosen methods, the goal being to obtain insights about the team’s circumstances. In general, the best results were obtained with structured methods, which simultaneously were also the least preferred by students, probably due to the ease of implementation associated with the alternative type of methods; namely, intuitive. Additionally, the study investigated other significant effects, such as the length of time of the experiments and the timing of each stage, as well as the effects of the particular context in which the experiment occurred. Considering the two types of methods, for example, an organization focused on structured methods could benefit from using those methods periodically, increasing its “tool dexterity” ability, while an organization focused on intuitive methods could emphasize the background of the users, namely the “user capacities”. Since those trends—and others—were similar for both problems in both contexts, it is natural to ask which changes could modify these tendencies. Changing the problem’s complexity and reaching to a more diverse universe of participants could be a good step towards having more confidence in the deduction of general design principles to generate ideas for solving real world challenges. © 2019, Springer-Verlag France SAS, part of Springer Nature.
Keywords: Design methods; Educational innovation; KJ technique; SCAMPER; TRIZ